Plataforma rcampus y su influencia en el aprendizaje colaborativo de los estudiantes de bachillerato de la unidad educativa “Francisco Huerta Rendón” del cantón Babahoyo. - López Torres, Yury Argentina (2017)
The present research work entitled "PLATFORM RCAMPUS AND ITS INFLUENCE ON THE COLLABORATIVE LEARNING OF THE BACHELOR STUDENTS OF THE EDUCATIONAL UNIT" FRANCISCO HUERTA RENDÓN "DEL CANTÓN BABAHOYO, aims to determine the influence of the Rcampus platform in the collaborative learning of the baccalaureate students of the educational unit "Francisco Huerta Rendón", of the Babahoyo canton, province of Los Ríos, during the 2017-2018 school year. Bibliographical, field and diagnostic research was used with the deductive and inductive method, its respective survey applied to teachers and students; With a sample of 185 participants, the results of the research identified the variables that intervene in the hypothesis. Conclusions were established where the educational platforms for collaborative learning have a relationship with education because it allows to improve the participation and interaction in the teaching-learning process, and to contribute the interest to learn, this way the student does not feel bored and be able to build their own knowledge, recommending teachers to implement interactive tools so that they awaken the interest to learn in the student and the teaching-learning process is of quality